2009
DOI: 10.4038/sljch.v32i3.706
|View full text |Cite
|
Sign up to set email alerts
|

Parental awareness on anti-epileptic treatment

Abstract: Objective To assess awareness on anti-epileptic therapy among parents of epileptic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Since all the interviewed parents were from the hospital clinics, we assume that information about epilepsy communicated to the parents at the time of diagnosis is inadequate or need more reinforcement to alleviate unnecessary parental worries and anxiety over their child [31]. Parents in our study showed good knowledge of antiepileptic medicine therapy [32]. Apparently, regular medication advice given during clinic visits and the perceived effectiveness of antiepileptic drugs prompted by recurrence of seizures with discontinuation are positive factors to maintain compliance to drug therapy.…”
Section: Discussionmentioning
confidence: 89%
“…Since all the interviewed parents were from the hospital clinics, we assume that information about epilepsy communicated to the parents at the time of diagnosis is inadequate or need more reinforcement to alleviate unnecessary parental worries and anxiety over their child [31]. Parents in our study showed good knowledge of antiepileptic medicine therapy [32]. Apparently, regular medication advice given during clinic visits and the perceived effectiveness of antiepileptic drugs prompted by recurrence of seizures with discontinuation are positive factors to maintain compliance to drug therapy.…”
Section: Discussionmentioning
confidence: 89%